(untitled) (Anclajes, 2013)
This article examines Nery Russo’s La mujer del caudillo (1952) in order to explore how this novel portrays the woman as a historical subject and especially how the scientific discipline called “History” and its notion of “truth” are treated in this text. In this regard, the following issues are highlighted: (1) the mechanisms that allow the author to present historiography as the partitioning of a significant exchange network formulated to regulate identities, and (2) the strategies by which Russo gives an account of herself in the Venezuelan cultural field in the early fifties, when the domestic role of Venezuelan women seemed mandatory.